ASSESSMENT OF PROGNOSTIC ASPECTS OF SHIRASHOOLA (HEADACHE) BY TAILA BINDU PARIKSHA - Priya, Monika; Rana, Deeksha; Chandra Kar, Anukul (International Journal of Psychosocial Rehabilitation, 2021)
Indian traditional medicine has a great history that describes ways to remain healthy, diagnostic methods of diseases, their treatment, and prognosis in detail. For proper diagnosis of diseases, Ayurveda has advised to examine patient’s different patho-physiological aspects through several methods, like Ashtasthana, Dasha Vidha, and Pariksha mentioned under Roga-Rogi Pariksha. MutraPariksha, mentioned under AshtasthanaPariksha, is an ancient method of urine examination. In the Ayurvedic classics, there is no direct description of methodology to ascertain the prognosis of Shirashoola (headache).TailaBinduPariksha, which is a part of MutraPariksha, is used to ascertain the prognosis of diseases. The International Headache Society (IHS) has developed a Headache Intensity Scale (HIS), which helps doctors and research scholars assess the intensity of headaches so that they may easily ascertain the functional capacity of a patient and the progress of disease. An open study was undertaken on a single group of 90 headache patients who were subjected to TailaBinduPariksha.The HIS score was also assessed and compared with shape and direction of spread. In the majority of the patients, the correlation was found to be statistically highly significant. TailaBinduParikshamay be used as an alternative method to ascertain the prognosis of headache patients.